2017 과민성장증후군의 임상진료지침 개정안 소개 - 정혜경; Hye-kyung Jung (The Korean journal of gastroenterology, 2018)
This guidance is an updated version of the irritable bowel syndrome (IBS) guidelines based on evidence-based medicine. IBS is a common chronic gastrointestinal syndrome that occurs in approximately 10% of the population and causes chronic abdominal pain as well as bowel habit changes, such as stool frequency or consistency. The final diagnosis of IBS is based on the exclusion of organic diseases that would explain the symptoms and the absence of endoscopic abnormalities. IBS can reduce the quality of life and cause a major disease burden, such as repeated examinations and continuous drug use, by mistaking organic diseases including malignancy. The major changes are as follows: 1) when to perform a colonoscopy under the impression of IBS; 2) effect of a low-fermentable oligosaccharides, disaccharides, monosaccharides, and polyol diet; 3) impact of probiotics in IBS; and 4) role of antibiotics in IBS. The Korean Society of Neurogastroenterology and Motility recently updated these guidelines to support physicians for qualified medical services and reduce the socioeconomic burden of IBS. (Korean J Gastroenterol 2018;72:252-257)